EVALUASI IMPLEMENTASI PROGRAM BINA PRIBADI ISLAMI (BPI) DALAM MEMPERKUAT KARAKTER SISWA SMA IT TUNAS BANGSA DENGAN MODEL CIPP - Refni, Evi; Priyanto, Sugeng; Badrujaman, Aip (Jurnal Administrasi Pendidikan Indonesia, 2025)
Efforts to shape student character require an in-depth study. During implementation, various problems have been identified that indicate a mismatch between the program objectives and students' actual behaviour. The purpose of this study is to analyse the rationale, resources, implementation, and results of the Islamic Personal Development (BPI) program in strengthening student character. The research method used is a mixed-method design, with data collected through interviews, observations, questionnaires, and documentation. The research subjects consisted of the principal, BPI coordinator, mentors, and students (mentees) in grades 10 and 11. The results of the study indicate that BPI implementation is quite effective but still needs improvement in several areas, especially in time management and interactions during coaching. The learning process, including BPI, which is also a form of learning, requires regular planning. This includes planning the curriculum and the mentors' teaching/mentoring workload. In addition, there is a need for a coaching guidebook that mentors and students can own. This research has implications for providing a reference for other Islamic educational institutions in designing character development strategies that are not only oriented towards cognitive aspects but also comprehensively address students' affective and spiritual domains.